Immediate impact of percutaneous transvenous mitral commissurotomy on right ventricular function - KC, Bishal; Malla, Rabi; Shah, Ram Kishore; Hirachan, Anish; Rauniyar, Binay Kumar; Limbu, Deepak; Gautam, Milan; Agrawal, Amit Kumar; Shareef, Miqdhaadh; Maskey, Arun; et al. (Nepalese Heart Journal, 2017)
Background and Aims: Abnormal Right Ventricular (RV) function affects the long term outcome and clinical symptoms in patients with mitral stenosis (MS). This study evaluates the immediate effect of Percutaneous Transmitral Commisurotomy (PTMC) on RV function. Methods: An observational, cross sectional study was done on 50 patients with rheumatic MS who underwent PTMC at Shahid Gangalal National Heart Center from Dec 2015 –Dec 2016. All underwent clinical evaluation and echocardiogram before and immediately after PTMC. Results: There was female preponderance with 66% being female. The mean age was 37.26 ± 10.63 years. There was immediate increase in the mitral valve area (MVA) from 0.87 ± 0.12cm2 to 1.54 ± 0.27cm2(p< 0.001). There was significant decrease in mean mitral diastolic gradient from 16.4 ± 8.8mmHg to 5 ± 1.5mmHg (p< 0.001), in the pulmonary artery systolic pressure 53.6 ± 21.83mmHg to 39.5 ± 14.67mmHg (p< 0.001), in the RV Tei index from 0.56 ± 0.08 to 0.40 ± 0.08 (p< 0.001). There was significant increase in TAPSE from 16.0 ± 1.50 to 18.6 ± 1.70 mm, (p<0.001) and the longitudinal velocity of excursion of the RV at the tricuspid annulus (RV S’) from 13.69 ± 3.33 cm/sec to 15.31 ± 3.07 cm/sec (p< 0.001) Conclusions: Successful PTMC can improve RV function as shown by the improvement in PASP, RV Tei index, TAPSE and RV S’. Further larger population studies are required to confirm the findings. Long term studies are important to determine the prognostic significance of improvement in RV function. Nepalese Heart Journal 2017; 14(2): 19-24